Association of peripheral NK cell counts with Helios+IFN‐γ– Tregs in patients with good long‐term renal allograft function. (13th March 2017) - Trojan, K.; Zhu, L.; Aly, M.; Weimer, R.; Bulut, N.; Morath, C.; Opelz, G.; Daniel, V.
Summary: Little is known about a possible interaction of natural killer (NK) cells with regulatory T cells (Treg ) in long‐term stable kidney transplant recipients. Absolute counts of lymphocyte and Treg subsets were studied in whole blood samples of 136 long‐term stable renal transplant recipients and 52 healthy controls using eight‐colour fluorescence flow cytometry. Patients were 1946 ± 2201 days (153–10 268 days) post‐transplant and showed a serum creatinine of 1·7 ± 0·7 mg/dl. Renal transplant recipients investigated > 1·5 years post‐transplant showed higher total NK cell counts than recipients studied < 1·5 years after transplantation ( P  = 0·006). High NK cells were associated with high glomerular filtration rate ( P  = 0·002) and low serum creatinine ( P  = 0·005). Interestingly, high NK cells were associated with high CD4 + CD25 + CD127 – forkhead box protein 3 (FoxP3 + ) Treg that co‐express the phenotype Helios + interferon (IFN)‐γ – and appear to have stable FoxP3 expression and originate from the thymus. Furthermore, high total NK cells were associated with Treg that co‐express the phenotypes interleukin (IL)−10 – transforming growth factor (TGF)‐β + ( P  = 0·013), CD183 + CD62L – ( P  = 0·003), CD183 + CD62 + ( P  = 0·001), CD183 – CD62L + ( P  = 0·002), CD252 – CD152 + ( P  < 0·001), CD28 + human leucocyte antigen D‐related (HLA‐DR – ) ( P  = 0·002), CD28 + HLA‐DR + ( P  < 0·001), CD95 + CD178 – ( P  < 0·001) and CD279 – CD152 + ( P  < 0·001), suggesting that these activated Treg home in peripheral tissues and suppress effector cells via TGF‐β and cytotoxic T lymphocyte‐associated protein 4 (CTLA‐4). The higher numbers of NK and Treg cell counts in patients with long‐term good allograft function and the statistical association of these two lymphocyte subsets with each other suggest a direct or indirect (via DC) interaction of these cell subpopulations that contributes to good long‐term allograft acceptance. Moreover, we speculate that regulatory NK cells are formed late post‐transplant that are able to inhibit graft‐reactive effector cells. Abstract : The higher numbers of NK and Treg cell counts in patients with long‐term good allograft function and the statistical association of these two lymphocyte subsets with each other suggest a direct or indirect (via DC) interaction of these cell subpopulations that contributes to good long‐term allograft acceptance.